2008
DOI: 10.1007/s00415-008-0780-3
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated auditory startle responses in patients with spinal cord injury

Abstract: The capability of the adult central nervous system to reorganize its circuits over time for improved functionality following injury is probably the key to understanding the increased ASRs in patients with SCI. The exaggeration of the startle reflex is potentially important since it may be useful for augmenting voluntary movement in the clinical rehabilitation of patients with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…However when TA coherence was measured for all the frequency bands studied (10–60 Hz), a significant velocity-dependent increase was noted for the SCI spasticity group, suggesting a generalised excitability of activity within the neuroaxis [22] including subcortical motor control systems [45]. Furthermore gamma intramuscular TA coherence was also higher at faster isokinetic speeds, but also correlated negatively with muscle hypertonia, similar to our previous study [22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However when TA coherence was measured for all the frequency bands studied (10–60 Hz), a significant velocity-dependent increase was noted for the SCI spasticity group, suggesting a generalised excitability of activity within the neuroaxis [22] including subcortical motor control systems [45]. Furthermore gamma intramuscular TA coherence was also higher at faster isokinetic speeds, but also correlated negatively with muscle hypertonia, similar to our previous study [22].…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly in a previous study we have shown that TA gamma band coherence in motor incomplete SCI patients correlates with severe spasticity symptoms, including spasms and hypertonia during isometric dorsiflexion [22]. Taken together, these studies suggest that increased activity within reticulospinal and/or propriospinal control mechanisms, without an increase in TA MEP (see below), could be mediated both adaptive and maladaptive neuroplasticity of subcortical motor control pathways after SCI [45]. …”
Section: Discussionmentioning
confidence: 86%
“…Closer neurophysiological analysis of the activity within these pathways after SCI should be made to provide more detailed evidence regarding both maladaptive neuroplasticity related to spasticity [68] and adaptive neuroplasticity related to recovery of residual motor function [69,70]. …”
Section: Discussionmentioning
confidence: 99%
“…The development of stretch hyperreflexia following SCI may depend on the alteration of descending control systems (Taylor et al, 1997), possibly to changes in the extrapyramidal brainstem circuits (Kumru et al, 2008), or to damage of the local lumbar neuronal circuits (Hefferan et al, 2007). Cutaneous hyperreflexia may also be mediated by disruption of descending motor control pathways constituted by the extrapyramidal motor system (Clarke et al, 2002) or cortically-mediated control mechanisms (Nielsen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%